Diverse roles of the nucleic acid‐binding protein KHSRP in cell differentiation and disease. (27th December 2015) - Briata, Paola; Bordo, Domenico; Puppo, Margherita; Gorlero, Franco; Rossi, Martina; Perrone‐Bizzozero, Nora; Gherzi, Roberto
Abstract : The single‐stranded nucleic acid‐binding protein KHSRP (KH‐type splicing regulatory protein) modulates RNA life and gene expression at various levels. KHSRP controls important cellular functions as different as proliferation, differentiation, metabolism, and response to infectious agents. We summarize and discuss experimental evidence providing a potential link between changes in KHSRP expression/function and human diseases including neuromuscular disorders, obesity, type II diabetes, and cancer. WIREs RNA 2016, 7:227–240. doi: 10.1002/wrna.1327 This article is categorized under: RNA Interactions with Proteins and Other Molecules > RNA–Protein Complexes RNA Turnover and Surveillance > Regulation of RNA Stability RNA in Disease and Development > RNA in Disease